Inquadramento sistematico del tema: principio di libera trasferibilità delle partecipazioni nella società a responsabilità limitata; disciplina e interessi sottesi - Di Bona, Laura (Cultura giuridica e diritto vivente, 2020)
[Conflict between multiple buyers of the same investment in s.r.l. and non domino configurability of the purchase]. Starting from the interpretation of the regulatory previsions of art. 2470, paragraph 3, cod. civ. - also in the light of the comparison with the discipline of conflicts between several buyers of movable property (art. 1155 of the civil code) and immovable property (art. 2644 of the civil code) - the essay proposes the application of the rules laid down therein with reference to the conflict between multiple buyers of the same shareholding in s.r.l. also to the hypothesis, not expressly provided, of the relative non domino purchase.